Multi-material printing of reaction bonded carbides by robocasting - Wahl, Larissa; Weichelt, Michelle; Travitzky, Nahum (Additive Manufacturing, 2021)
In the present work, reaction bonded boron carbide (RBBC) and reaction bonded silicon carbide (RBSC) composites were fabricated using multi-material robocasting followed by liquid silicon infiltration (LSI). The fabrication of carbide based materials using LSI is of great technological interest because it avoids the need for the relatively high temperatures and pressures required in traditional fabrication. Multi-material robocasting offers the possibility of combining materials and thus their properties, as demonstrated in this work with silicon carbide (SiC) and boron carbide (B4C). The feasibility of combining RBSC and RBBC was demonstrated by printing multilayer bending bars and more complex structures. The microstructure of the samples was investigated and, in particular, the interface between the different layers at each processing step was studied. After LSI, cracks were observed in the B4C layers due to differences in thermal expansion, but the interfaces showed no delamination and good interfacial bonding between the layers was evident. Hardness measurements were performed to investigate the interfacial bonding and residual stresses in the materials used. The manufactured RBSC and RBBC samples with a relative density of 99% and 98%, showed a hardness of 18.3 GPa and 17.1 GPa, respectively, which are within the range of the reference data from the literature. The residual stresses in the layers were calculated theoretically and also based on the crack pattern generated by Vickers indentation. Tensile stresses in RBBC and compressive stresses in RBSC were determined and can explain the cracking in the laminated structures.
CRIS-Team WoS Importer:2021-12-31